1982
DOI: 10.1021/om00072a006
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and reactions of a cationic hydrido(hydroxymethyl)iridium complex. The crystal and molecular structure of hydrido(hydroxymethyl)tetrakis(trimethylphosphine)iridium(III) hexafluorophosphate, [IrH(CH2OH) (PMe3)4][PF6]

Abstract: Syntheses and Reactions of a Cationic Hydrido(hydroxymethyl)iridium Complex. The Crystal and Molecular Structure of Hydrido(hydroxy methyl)tetrakis(trimethy Iphosphine) iridium (III) Hexafluorophosphate, [IrH(CH2OH)(PMe3)4][PF6p

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 11 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Compound 6 has been fully characterized by NMR, including 2D experiments. The obtained spectra confirm the formation of the hydroxyalkyl groups bonded to rhodium, , trans to the phosphorus atom of the acyl−phosphine chelate. The 13 C resonances appear in the 93−97 ppm range as doublets of doublets due to coupling with rhodium ( J (Rh,C) = 22 Hz) and with a trans phosphorus atom ( J (P,C) = 98 Hz).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 6 has been fully characterized by NMR, including 2D experiments. The obtained spectra confirm the formation of the hydroxyalkyl groups bonded to rhodium, , trans to the phosphorus atom of the acyl−phosphine chelate. The 13 C resonances appear in the 93−97 ppm range as doublets of doublets due to coupling with rhodium ( J (Rh,C) = 22 Hz) and with a trans phosphorus atom ( J (P,C) = 98 Hz).…”
Section: Resultsmentioning
confidence: 99%
“…Complex 6 shows lower stability than the related compound [Rh(PPh 2 ( o -C 6 H 4 CO))(PPh 2 ( o -C 6 H 4 CHOH))(bdh)]BPh 4 ,15a containing a better donor ligand such as the bidentate diimine instead of pyridine and chloride. This is not surprising,12a but the usual decomposition paths reported for hydroxyalkyl complexes include regeneration of the M−H bond and free aldehyde or, if an acid is added, disproportionation with hydride transfer to yield an acyl and an alkyl complex. , No presence of 5 was observed in the NMR spectra recorded during the transformation of 6 into 8 , thus excluding the reversal of 6 into 5 .
3
…”
Section: Resultsmentioning
confidence: 99%
“…Many hydroxymethyl complexes have now been synthesized and studied. 29,30,31,[33][34][35][36][37][38][39][42][43][44][45][46][47][48][49][50][51][52][53] Berke and Huttner51 first showed that CO migratory insertion into the metalhydroxymethyl bond occurs in the unstable complex Fe-(CO)2[P(OMe)3]2(Cl)(CH2OH). An isolated metallacyclic rhenium hydroxyalkyl complex was later shown by Gla-dysz53 to react with CO (eq 4).…”
Section: M-cmentioning
confidence: 99%
“…Indeed, PMe3 dissociation from this complex is very difficult. 4 In addition, the Ir"' complexes that would be formed by attack at the metal, (PMe3)41r(R)(SiMe3)+ are expected to be stable towards Si-R reductive elimination at 25°C. For example, heating at 100°C is required in order to cause reductive elimination from mer-(PMe3)31r(H)(SiR3)(Me) (R = Et, Ph, Et0).6 Also, (PMe3)41rMe(H)+ is thermally stable.2…”
mentioning
confidence: 99%